Australian species of Ommatius Wiedemann (Diptera: Asilidae) with an anepimeral bristle - Daniels, Greg (Zootaxa, 2017)
The presence of an anepimeral bristle in Australian Ommatius Wiedemann species is newly recorded and descriptions of seven new species possessing this character are presented: O. aquilonaris sp. nov., O. burwelli sp. nov., O. imaginis sp. nov., O. limbatus sp. nov., O. melasmus sp. nov., O. musselbrookensis sp. nov. and O. radamnis sp. nov. All species occur in Queensland but O. melasmus sp. nov. also occurs in New South Wales and O. musselbrookensis sp. nov. also occurs in the Northern Territory. A key to separate the species is presented.